Observations on arbuscular mycorrhiza associated with important edible tuberous plants grown in wet evergreen forest in Assam, India - RAJESH KUMAR; ASHWANI TAPWAL; SHAILESH PANDEY; RAJA RISHI; DEVAPOD BORAH (Society for Indonesian Biodiversity, 2013)
Kumar R, Tapwal A, Pandey S, Rishi R, Borah D. 2013. Observations on arbuscular mycorrhiza associated with important edible tuberous plants grown in wet evergreen forest in Assam, India. Biodiversitas 14: 67-72. Non-timber forest products constitute an important source of livelihood for rural households from forest fringe communities across the world. Utilization of wild edible tuber plants is an integral component of their culture. Mycorrhizal associations influence the establishment and production of tuber plants under field conditions. The aim of present study is to explore the diversity and arbuscular mycorrhizal (AMF) colonization of wild edible tuber plants grown in wet evergreen forest of Assam, India. A survey was conducted in 2009-10 in Sunaikuchi, Khulahat, and Bura Mayong reserved forest of Morigaon district of Assam to determine the AMF spore population in rhizosphere soils and root colonization of 14 tuberous edible plants belonging to five families. The results revealed AMF colonization of all selected species in all seasons. The percent colonization and spore count was less in summer, moderate in winter and highest in rainy season. Seventeen species of arbuscular mycorrhizal fungi were recorded in four genera viz. Acaulospora (7 species), Glomus (5 species), Sclerocystis (3 species) and Gigaspora (2 species).